Nephroureterectomy versus pyeloplasty for giant hydronephrosis in children with upper urinary tract obstruction; perspectives from a tertiary health facility in Southern Nigeria - Okoro, Philemon E.; Ekeke, Ngozi O. (International Surgery Journal, 2018)
Background: Unrecognized or neglected cases of obstructed upper urinary tract in children can cause marked dilatation and structural damage to the ureters and kidney/s. In our region, many of such unrecognized obstructions result in giant hydronephrosis with resultant poor outcomes of pyeloplasty. We present our perspective of such giant hydronephrosis and make a case for straight nephroureterectomy rather than pyeloplasty which has been our standard treatment. Methods: This is a review of cases of congenital upper urinary tract obstruction with giant hydroureteronephrosis seen in children in our practice between March 2008 and February 2017. Case notes of patients who were managed within the period were retrieved to extract relevant data. Data obtained included the biodata, presenting features, dimension of renal pelvis and ureter at imaging and intraoperatively, treatment offered, outcome as at one-year follow-up. Results were subjected to simple statistical analysis. Results: There were 39 patients and they comprised 22 (56.4%) males and 17 (43.6%) females. Their age range was 3 to 14 years with a mean of 7 years. The most consistent clinical feature was abdominal distension. Five (12.8%) patients had abnormality of renal function preoperatively. The obstruction was unilateral in 30 (76.9%) cases and bilateral in 9 (23.1%) cases giving a total of 48 obstructions. All the patients were operated on. Complications encountered were mostly related to patients in whom we performed pyeloplasty. There were three mortalities related to sepsis and end stage renal disease. Conclusions: Upper urinary tract obstruction is often recognized late in our practice. Abdominal swelling is a common presenting feature of upper urinary tract obstruction in our practice. It appears that in unilateral cases, nephroureterectomy is a safer and more effective treatment option than pyeloplasty in such late cases with giant hydronephrosis. There is need for a well-designed prospective study to evaluate the option of nephroureterctomy in these cases.